Kumar versus Olsen cannulation technique for intraoperative cholangiography: a randomized trial. - Buddingh, K; Bosma, B; Samaniego-Cameron, B; ten Cate Hoedemaker, H; Hofker, H; Dam, v; Ploeg, R; Nieuwenhuijs, V (2013)
BACKGROUND: There is resistance to routine intraoperative cholangiography (IOC) during cholecystectomy because it prolongs surgery and may be experienced as cumbersome. An alternative instrument may help to reduce these drawbacks and lower the threshold for IOC. This trial compared the Kumar cannulation technique to the more commonly used Olsen clamp for IOC (KOALA trial; Dutch Trial Register NTR2582). METHODS: Patients undergoing elective laparoscopic cholecystectomy were randomized between IOC using the Kumar clamp and the Olsen clamp. Primary end points were the time that the IOC procedure took and its perceived ease as measured on a visual analog scale from 0 (impossible) to 10 (effortless). To detect a difference of 33 % in IOC time, a total sample size of 40 patients was required. RESULTS: Fifty-nine patients were randomized. Nine were excluded because of conversion to open cholecystectomy before the IOC procedure. Twenty-eight patients underwent IOC with the Kumar clamp and 22 with the Olsen clamp. The success rate was 23 (82.1 %) of 28 for the Kumar clamp and 19 (86.4 %) of 22 for the Olsen clamp (p > 0.999). The mean IOC time was 10 min 27 s ± 6 min 17 s using the Kumar clamp and 11 min 34 s ± 7 min 27 s using the Olsen clamp (p = 0.537). Surgeons graded the ease of the Kumar clamp as 6.8 ± 2.7 and the Olsen clamp as 6.8 ± 2.1 (p = 0.977). CONCLUSIONS: IOC using the Kumar clamp was neither faster nor easier than using the Olsen clamp. Both clamps facilitated IOC in just over 10 min. Individual surgeon preference should dictate which clamp is used.